Circulating miRNAs in type 2 diabetic patients with and without Albuminuria in Malaysia - Zahari Sham, Siti Yazmin; Ng, Chin Tat; Amin-ul-Rashid, Shamin Azwar; Yip, Wai Kien; Abdullah, Maha; Thevandran, Kalaiselvam; Osman, Malina; Seow, Heng Fong (Karger Publishers, 2021)
Introduction: Diabetic kidney disease (DKD) remains the leading cause of chronic kidney disease. Dysregulation of circulating miRNAs has been reported, suggesting their pathological roles in DKD. This study aimed to investigate differentially expressed miRNAs in the sera of type 2 diabetes mellitus (T2DM) patients with and without albuminuria in a selected Malaysian population. Method: Forty-one T2DM patients on follow-up at a community clinic were divided into normo-(NA), micro-(MIC), and macroalbuminuria (MAC) groups. Differential levels of miRNAs in 12 samples were determined using the pathway-focused (human fibrosis) miScript miRNA qPCR array and was validated in 33 samples, using the miScript custom qPCR array (CMIHS02742) (Qiagen GmbH, Hilden, Germany). Results: Trends of upregulation of 3 miRNAs in the serum, namely, miR-874-3p, miR-101-3p, and miR-145-5p of T2DM patients with MAC compared to those with NA. Statistically significant upregulation of miR-874-3p (p = 0.04) and miR-101-3p (p = 0.01) was seen in validation cohort. Significant negative correlations between the estimated glomerular filtration rate (eGFR) and miR-874-3p (p = 0.05), miR-101-3p (p = 0.03), and miR-145-5p (p = 0.05) as well as positive correlation between miR-874-3p and age (p = 0.03) were shown by Pearson’s correlation coefficient analysis. Conclusion: Upregulation of previously known miRNA, namely, miR-145-5p, and possibly novel ones, namely, miR-874-3p and miR-101-3p in the serum of T2DM patients, was found in this study. There was a significant correlation between the eGFR and these miRNAs. The findings of this study have provided encouraging evidence to further investigate the putative roles of these differentially expressed miRNAs in DKD.